Proceedings of the conference on biodiversity conservation and ultilisation : (Radet for U-Landsforskning, 1999)
This book consists of the following many parts such as the rapid changes surrounding biodiversity policy, implementation and mangement aimed at helping development countries to achieve a more equitable sharing of thier biological and genetic resources.